Analysis of digital track receiver of tonal rail circuits - Honcharov, K. V. (Science and Transport Progress, 2011)
In the paper the practicability of using the digital signal processing in track receivers of the tone track circuits is shown. On the basis of spectral analysis results of the signal current of the tone track circuits, as well as with taking the acting standards into account, the requirements to frequency features of digital filters for the track receiver are formulated, and the syntheses of such filters are conducted. A simulation modeling of the synthesized digital receiver has confirmed its correspondence to the requirements of existing departmental normative documents.